MODERN TRENDS OF THE SUSTAINABLE DEVELOPMENT OF SUBSOIL USING AT THE MINERAL-RESOURSES CENTRES OF ECONOMICAL GROUWTH - Jikalak, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Development of mineral industry in Ukraine up to 2030 will be conduction in terms of globalization and influence of internal and international competition in the area of mineral commodities and their markets. For long-term stable development of Ukrainian economy based on essential mineral commodities, research-based government mineral police is needed/ It should be realized on the basis of minerals supply/demand balance, in the circumstances of free market economy.